2021
DOI: 10.1016/j.neo.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

p85β alters response to EGFR inhibitor in ovarian cancer through p38 MAPK-mediated regulation of DNA repair

Abstract: EGFR signaling promotes ovarian cancer tumorigenesis, and high EGFR expression correlates with poor prognosis. However, EGFR inhibitors alone have demonstrated limited clinical benefit for ovarian cancer patients, owing partly to tumor resistance and the lack of predictive biomarkers. Cotargeting EGFR and the PI3K pathway has been previously shown to yield synergistic antitumor effects in ovarian cancer. Therefore, we reasoned that PI3K may affect cellular response to EGFR inhibition. In this study, we reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
0
6
1
Order By: Relevance
“…For ERL, Kryeziu et al [ 65 ] showed that 20 µM ERL did not induce DNA damage (alkaline comet assay) in A549 cells after 6 h exposure [ 65 ]. Contrary to this and our study, Mak et al [ 66 ] showed that ERL (10 µM) increases the percentage of tail DNA in human ovarian cancer cells (SKOV-3 cells), but only after a longer exposure time (72 h).…”
Section: Resultscontrasting
confidence: 99%
“…For ERL, Kryeziu et al [ 65 ] showed that 20 µM ERL did not induce DNA damage (alkaline comet assay) in A549 cells after 6 h exposure [ 65 ]. Contrary to this and our study, Mak et al [ 66 ] showed that ERL (10 µM) increases the percentage of tail DNA in human ovarian cancer cells (SKOV-3 cells), but only after a longer exposure time (72 h).…”
Section: Resultscontrasting
confidence: 99%
“…To this end, we first performed GOEA considering all 549 driver genes (Supplementary Table 08) and then reconstructed the specific activation time of each significant GO term by calculating the proportion of genes it included from each cluster. GOEA analysis of the 549 driver genes (Figure 4B) revealed several biological processes previously linked to drug resistance in other cancer types, including lysosome biogenesis, Reactive Oxygen Species (ROS) homeostasis, and fatty acid metabolism (48)(49)(50)(51)(52)(53)(54), as well as specific genes linked to EGFR resistance, such as PDGF-C (55), FGF2 (56,57), PIK3R2 (58), HRAS (59), MAPK3 (60,61), GAS6 (62), and BAX (63) (Figure 4C). Interestingly, PDGF-C and FGF2 are PDGFR-α and FGFR ligands, respectively.…”
Section: Temporal Analysis Of Afatinib-mediated Transcriptional Progr...mentioning
confidence: 99%
“…Additionally, p38ɑ directly phosphorylates and activates CtIP, which is responsible for DNA double-strand break resection and proper DNA repair [ 96 ]. Moreover, activated p38 MAPK signaling increases the expression levels of BRD4 and 53BP1 (key DNA damage response factors that promote nonhomologous end joining repair), thereby repairing damaged DNA and protecting cells from apoptosis [ 97 ]. p38 inhibition could be utilized to prevent the activation of cell-cycle checkpoints, particularly the G2 checkpoint, and DNA repair pathways in order to increase the accumulation of DNA damage in CSCs, resulting in induction of apoptosis.…”
Section: Mechanisms Of P38-mediated Chemoresistancementioning
confidence: 99%